From Myth to History: The Emergence of Historiographical Tradition in China - Muhametzyanov, Rustem Ravilevich; Usmanova, Ilina Radikovna; Somkina, Nadezhda Alexandrovna (Journal of History Culture and Art Research, 2019)
The Chinese civilization, despite having experienced many historical shocks, shows consistency in its sociocultural institutions and adherence to traditional values which were formed in ancient times. Many experts claim the Chinese people’s deep knowledge and respect for their history is one of the reasons for China’s cultural consistency. The worship of antiquity is one of the important characteristics traced in many spheres of Chinese history. In this paper, we will elaborate on the issue of the basis for the emergence of this worship. The studied phenomenon arose during the Zhou period and was strengthened by Confucius and his disciples. Since then, antiquity worship hasn’t been revised by society. The formation of antiquity worship in traditional China went gradually, and a total reshaping of Ancient China’s spiritual life was needed for that. In this research, we will try to find out how this worship came to be. Such analysis is not only interesting for the studies of Chinese civilization but also for the research of the specifics of the Middle Kingdom’s spiritual culture. The analysis of cultural specifics of China must help uncover the mechanisms of this civilization’s consistency.